Use of High-Voltage Pulsed Electric Fields for the Preservation of Fresh Foods - Li Nan; Wang Yongrui; Yang Han (BIO Web of Conferences)
Today, China’s productivity is steadily growing, and the output of agricultural and sideline products is also increasing. There is an increasing need for the preservation of fresh foods such as vegetables that are not consumed immediately after harvest or sale. Electric field technology, as a new method of preservation, features the advantages of extending the shelf life, being sustainable, pollution-free, and consuming less energy. Compared to traditional preservation methods, it better meets modern demands for healthy, green food. This article evaluates the effects of high-voltage pulsed electric field treatment on the preservation of fresh milk and carrot juice through experimental verification. The study found that within the range of output voltages from 20kV to 30kV, output frequencies from 100Hz to 200Hz, and treatment times from 1 minute to 2 minutes, the factor that most significantly affects the high-voltage pulse electric field sterilization and preservation effect is the output frequency, while the impact of the output voltage is not significant. Based on the results, the paper discusses the potential applications and future prospects of electric field technology in the field of food preservation, providing suggestions and directions for future research and application.